Introduction to the Special Issue: Everyday Self-Employment. (February 2019) - Cohen, Rachel Lara; Hardy, Kate; Valdez, Zulema
A "partial renaissance" of self-employment in labor markets of the global North has attracted policy concern within national, supranational, and global arenas, yet sociological thought has been somewhat slower to respond to this phenomenon. In response, this special issue focuses on everyday self-employment among workers drawn from countries across the world. The collection of articles in this volume originated, in part, from a recent symposium that took place at City, University of London, which highlighted the contribution of sociology and cognate disciplines to the study of self-employment. The volume considers the social and structural forces that condition this economic activity as an ideology and practice, as well as the constraints and opportunities for its maintenance and reproduction. It also examines the everyday lives of self-employed workers and in particular the ways in which self-employment is experienced across a range of geographical, occupational, and industrial contexts, and with regard to social categories including race, class, nationality, and gender. As neoliberal subjects, we are increasingly required to inhabit an entrepreneurial self. As such, a sociological understanding of the global patterns and everyday experiences of self-employment—or entrepreneurialism as practice—and the cultural legitimations associated with this oft-celebrated and aspirational economic activity are essential to a critical understanding of the economy and society. What are the current national and international trends in self-employment? What characteristics distinguish entrepreneurs from small-business owners or self-employed workers? If the image of an entrepreneur is an economically mobile rugged individualist, how do social relationships shape entrepreneurialism among transnational migrants or dependent visa holders? Is financial remuneration or maximizing profit always the primary goal, or are the self-employed from different social locations motivated by other, nonpecuniary benefits, such as spiritual fulfillment? Might vulnerable populations, such as undocumented immigrants, have the less lofty goal of basic survival? How is self-employment organized across different occupations? Can self-employment function as a strategy of collective resistance or subversion? The contributors in this volume often challenge mainstream views of self-employment and entrepreneurship to reveal the complexity and scope of self-employed activity; their perspectives provide new insights for researchers and policy- makers regarding the function of self-employment in a changing economy and society. This introduction initiates a discussion of the central debates in the study of self-employment and presents a brief synopsis of the articles in this volume.